The economic burden of individuals living with generalized myasthenia gravis and facing social determinants of health challenges - Hughes, Tom; Howard, James F.; Silvestri, Nicholas J.; Anderson, Ashley E. L.; Sato, Mai; Suchotliff, Sharon; Guptill, Jeffrey T.; Phillips, Glenn (Frontiers in Public Health, 2023)
Objective: Better understanding the impact of social determinants of health (SDOH) barriers from the patient perspective is crucial to improve holistic patient support in generalized myasthenia gravis (gMG), a rare autoimmune disorder with high disease and treatment burden. The objective of this study was to identify economic challenges experienced by individuals living with gMG and SDOH barriers to better address current unmet needs. Methods: Adults (18−75 years) living with gMG and experiencing SDOH barriers in the United States were recruited to a mixed-methods study including qualitative interviews and a web-based quantitative survey. Quotas were implemented to include a balanced spread of baseline demographic categories including insurance type, living environment, and employment status among the study sample. Direct and indirect economic challenges were identified by degree of concern. Results: The survey was completed by 38 individuals living with gMG, the majority of whom were enrolled in public insurance and not employed. The most commonly reported major economic concerns were managing funds for emergency care (66%), loss of income (61%), and non-medical expenses (58%), highlighting the diversity of economic challenges. Individuals who were using public insurance plans, living in non-urban environments, and unemployed experienced pronounced challenges around managing non-medical costs and accessing government assistance. Conclusion: Both direct and indirect costs were emphasized as major concerns among individuals living with gMG and SDOH barriers. Increasing access to relevant, personalized, and holistic resources, including care management, should be prioritized to improve disease management and outcomes for individuals living with gMG.